2019
DOI: 10.1080/09640568.2019.1613221
|View full text |Cite
|
Sign up to set email alerts
|

The regional heterogeneity of wind power deployment: an empirical investigation of land-use policies in Germany and Sweden

Abstract: The purpose of this paper is to analyze and compare the impacts of land-use policies on wind power deployment at the regional levels in Germany and Sweden. We use data for the period 2008-2012, and an econometric approach in which the probability of having any wind power capacity additions and the actual level of increased capacity, given that it is positive, are permitted to be determined by different processes. The results confirm the importance of land-use policies, e.g., priority and exclusion areas, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 41 publications
1
19
1
1
Order By: Relevance
“…This finding is in contradiction to most existing studies (e.g. Goetzke and Rave, 2016;Lauf et al, 2018), which confirmed land area and population density (together with wind potential) best predict the installed capacity. Significant correlations have not been found between installed capacity and the intensity of landscape protection and the use of land in the area (the share of nature and landscape protected areas, forests and agricultural land in Tab.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…This finding is in contradiction to most existing studies (e.g. Goetzke and Rave, 2016;Lauf et al, 2018), which confirmed land area and population density (together with wind potential) best predict the installed capacity. Significant correlations have not been found between installed capacity and the intensity of landscape protection and the use of land in the area (the share of nature and landscape protected areas, forests and agricultural land in Tab.…”
Section: Resultscontrasting
confidence: 99%
“…A comparative study by Lauf et al (2018) found that regional variations in wind power deployment in Sweden and Germany, to a significant extent, can be attributed to land-use policies, not least in the form of priority areas and the designation of restricted areas. This study also confirmed a positive correlation of wind capacity with the land area and a negative correlation with population density.…”
Section: Spatial Differentiation and The Uneven Development Of Renewamentioning
confidence: 99%
See 1 more Smart Citation
“…The result presented in Figure 7 shows that especially the southern part of Sweden has large areas covered by infrastructure, making it harder to find land for onshore wind projects. This regional heterogeneity in Sweden has previously been discussed by [23] and is further verified by this study. The study furthermore addresses the risks associated with wind project development and maps several of the risks presented by [26].…”
Section: Journal Of Renewable Energysupporting
confidence: 90%
“…Even though this is not considered a restriction, we also considered applying restriction areas for existing operating wind turbines, as repowering of the existing wind farms will be a future option. The same goes for areas of national interest, as [23] indicated that national interests do not result in actual restrictions due to the lack of strong political definitions and tools for defining these areas.…”
Section: Lakesmentioning
confidence: 93%